Strategi Merek Berbasis Identitas Lokal Kerajaan Kendan Pada Desa Wisata Citaman - Made Ayu Adinda Prima Dewi; Wirania Swasty; Ira Wirasari (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Citaman Village, Nagreg District, Bandung Regency, holds potential in agrotourism, local historical tourism of the Kendan Kingdom, and culinary tourism, yet recorded only 614 tourist visits in 2024 due to a brand identity limited to a logo without an integrated system. This study aims to identify brand elements used by selected tourism villages in West Java as a reference for Citaman Village, analyze the causes of the suboptimal brand strategy, and formulate a local identity-based brand strategy. A qualitative approach was employed using the Strategic Design and Design Thinking frameworks. Data were collected through visual audits, in-depth interviews, and document analysis, then analyzed using thematic analysis, PEST, and SWOT. The findings indicate that: (1) selected tourism villages in West Java consistently implement six integrated brand elements encompassing brand identifiers, color palettes, typography, photography, graphic elements, and implementation across digital and physical media, (2) weakened community social capital including the absence of structured promotion, a tourism workforce regeneration crisis, and a generational shift in aspirations toward the industrial sector constitutes the root cause of the suboptimal brand strategy in Citaman Village, and (3) the local historical identity of the Kendan Kingdom fulfills the criteria of authenticity, uniqueness, and emotional relevance as a foundation for sustainable brand differentiation. Based on these findings, a Brand Guideline grounded in a visual identity system was formulated as both a social empowerment instrument and a strategy to build brand awareness. This study does not empirically measure tourist brand awareness, but rather formulates a strategy as a systematic foundation to be developed in future research.